Design of a Servo-Controlled Variable Resistor - Muhammad Ikhsan; Syukri, Syukri (Aceh Journal of Electrical Engineering and Technology, 2025)
This study develops an innovative servo-controlled variable resistor to address the need for precise programmable resistance in modern electronics. While manual potentiometers lack automation capability and digital versions introduce quantization errors, the proposed hybrid solution combines microcontroller-driven servo mechanisms with standard rotary potentiometers, preserving analog quality with digital control. Through experimental methodology involving system design, hardware implementation, and software development, the author created and tested an electronically adjustable resistor system. Rigorous evaluation across 738 trials demonstrated exceptional performance: average standard deviation of 0.009, data range of 0.07, and coefficient of variation (CV) of 0.564%, approaching Six Sigma precision (3.4 defects per million). Statistical analysis confirmed the system's stability and repeatability, outperforming both manual adjustment (typical CV >5%) and digital alternatives. The results establish our servo-controlled design as a superior solution, offering precise programmability without compromising analog signal integrity. This advancement enables new applications in automated testing, and adaptive circuits where traditional variable resistors prove inadequate. The research contributes a reliable control mechanism for analog components while setting quantitative benchmarks for programmable resistance systems.